A deuterated composition, organic electroluminescent device and display device
Patent Information
- Application Number
- CN202210906094.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-07-29
AI Technical Summary
[0062]本发明中通过对氘代组合物组成的设计,进一步通过选用具有特定结构式的化合物的共同使用,并以此氘代组合物作为OLED发光器件有机薄膜层材料,使得OLED发光器件具有较低的驱动电压、较高的电流效率和较长的寿命。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electroluminescent materials technology, specifically relating to a deuterated composition, an organic electroluminescent device, and a display device. Background Technology
[0002] Currently, organic light-emitting diode (OLED) display technology has been applied in smartphones, tablets, and other fields, and will further expand to large-size applications such as televisions. Over the past 30 years of development, various high-performance OLED materials have been developed. Through different designs of device structures and optimization of device lifespan, efficiency, and other performance characteristics, the commercialization of OLEDs has been accelerated, leading to their widespread application in display and lighting fields.
[0003] The selection of materials for the hole layer, emissive layer, and other organic functional layers also significantly impacts the device's current efficiency, driving voltage, and lifetime. Currently, the exploration of functional layer materials with higher performance is ongoing. Therefore, to meet the increasingly demanding requirements for OLED devices, the field urgently needs to develop a wider variety of higher-performance OLED materials. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a deuterated composition, an organic electroluminescent device, and a display device. The deuterated composition provided by the present invention can be used as an organic thin film layer material for organic electroluminescent devices, thereby improving the performance of the organic electroluminescent devices.
[0005] To achieve this objective, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a deuterated composition comprising at least two compounds, each having a structure as shown in Formula I:
[0007]
[0008] In this case, either X or Y is N, and the other is CR;
[0009] R and Ar1 are each independently selected from any one of C6-C40 aryl and C3-C20 heteroaryl groups;
[0010] m and n are each independently selected from 0 or 1, and m and n are not both 0 at the same time;
[0011] The hydrogen atom in the compound shown in Formula I can be substituted by at least one of the following: deuterium atom, -F, -CN, C6-C20 aryl, C6-C20 heteroaryl, C1-C6 alkyl, and C1-C6 alkoxy.
[0012] The compound shown in Formula I meets at least one of the following conditions:
[0013] (1) The compound shown in Formula I does not contain deuterium atoms;
[0014] (2) In the compound shown in formula I All hydrogen atoms in the group are replaced by deuterium atoms;
[0015] (3) In the compound shown in Formula I, at least one hydrogen atom in the Ar1 group is replaced by a deuterium atom;
[0016] (4) In the compound shown in Formula I for Group;
[0017] (5) At least one hydrogen atom in the R group is replaced by a deuterium atom;
[0018] (6) In the compound shown in Formula I, the hydrogen atoms are replaced by C6-C20 aryl groups, and at least one hydrogen atom in the C6-C20 aryl group is replaced by a deuterium atom.
[0019] (7) The hydrogen atoms in the compound shown in Formula I are replaced by C1-C6 alkyl and / or C1-C6 alkoxy groups, and all hydrogen atoms in the C1-C6 alkyl and / or C1-C6 alkoxy groups are replaced by deuterium atoms.
[0020] Dashed lines indicate connection points;
[0021] The at least two compounds having the structure shown in Formula I include at least one of the Formula I compounds that meet any one of conditions (2) to (7).
[0022] In this invention, by designing a deuterated composition and using it as an organic thin film layer material in an organic electroluminescent device, an organic electroluminescent device with lower driving voltage, higher current efficiency, and longer lifetime can be obtained.
[0023] It should be noted that if m is 1 and n is 0 in this invention, then Ar1 is selected from C6-C40 aryl or C3-C20 heteroaryl; if both m and n are 1, then Ar1 is the corresponding disubstituted group, that is, Ar1 is selected from C6-C40 arylene or C3-C20 heteroarylene.
[0024] In this invention, C6-C40 can be C6, C8, C10, C12, C16, C20, C24, C28, C30, C32, C36 or C40, etc.
[0025] The C3-C20 can be C3, C6, C10, C12, C16, or C20, etc.
[0026] The hydrogen atom in the compound shown in Formula I may be substituted by at least one of -D (deuterium atom, the same below), -F, -CN, C6-C20 (e.g., C6, C10, C12, C16 or C20), C6-C20 (e.g., C6, C10, C12, C16 or C20), C1-C6 (e.g., C1, C2, C3, C4, C5 or C6), and C1-C6 (e.g., C1, C2, C3, C4, C5 or C6) alkyl, or C1-C6 (e.g., C1, C2, C3, C4, C5 or C6) alkoxy.
[0027] In this invention, condition (3) is further preferably: when Ar1 in the compound shown in Formula I is selected from a single aromatic ring, such as phenylene or naphthylene, all hydrogen atoms on the single aromatic ring are replaced by deuterium atoms; when Ar1 in the compound shown in Formula I is composed of two or more aromatic rings, all hydrogen atoms on at least one aryl group are replaced by deuterium atoms, for example, when Ar1 is selected from biphenylene, all hydrogen atoms on at least one phenyl group are replaced by deuterium atoms; when Ar1 is selected from phenylene naphthalene, all hydrogen atoms on the phenyl and / or naphthyl groups are replaced by deuterium atoms.
[0028] In this invention, condition (5) is further preferably: when R in the compound shown in Formula I is selected from a single aromatic ring, such as phenyl or naphthyl, all hydrogen atoms on the phenyl or naphthyl group are replaced by deuterium atoms; when R in the compound shown in Formula I is composed of two or more aromatic rings, all hydrogen atoms on at least one aryl group are replaced by deuterium atoms, for example, when R is selected from biphenyl, all hydrogen atoms on at least one phenyl group are replaced by deuterium atoms; when R is selected from phenylnaphthalene, all hydrogen atoms on the phenyl and / or naphthyl groups are replaced by deuterium atoms.
[0029] In this invention, condition (6) is further preferably: when the C6-C20 aryl group in the compound of formula I is selected from a single aromatic ring, such as phenyl or naphthyl, all hydrogen atoms on the phenyl or naphthyl group are replaced by deuterium atoms; when the C6-C20 aromatic ring in the compound of formula I is composed of two or more aryl groups, all hydrogen atoms on at least one aryl group are replaced by deuterium atoms, for example, when the C6-C20 aryl group is selected from biphenyl, all hydrogen atoms on at least one phenyl group are replaced by deuterium atoms; when the C6-C20 aryl group is selected from phenylnaphthalene, all hydrogen atoms on the phenyl and / or naphthyl groups are replaced by deuterium atoms.
[0030] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0031] As a preferred embodiment of the present invention, the C3-C20 heteroaryl group is selected from any one of C3-C20 (e.g., C3, C6, C10, C12, C16, or C20, etc.) nitrogen-containing heteroaryl groups, dibenzofuranyl, dibenzothiophene, naphthobenzofuranyl, or dibenzothiophene.
[0032] As a preferred embodiment of the present invention, R and Ar1 are each independently selected from any one of phenyl, biphenyl, naphthyl, phenanthryl, anthracene, fluorenyl, benzo[a]fluorenyl, dibenzo[a]fluorenyl, triphenylene, fluoranyl, pyrene, perylene, spirofluorenyl, pyridyl, pyrazinyl, pyrimidinyl, triazinyl, quinolinyl, isoquinolinyl, quinoxalinyl, quinazolinyl, imidazolyl, benzimidazolyl, indo[a]fluorenyl, or hydrogenated benzirthalyl.
[0033] As a preferred embodiment of the present invention, R is selected from triphenylene, phenyl, naphthyl, diphenyl, 9,9-dimethylfluorenyl, fluoranyl, dibenzofuranyl, dibenzothiopheneyl, naphthobenzofuranyl, benzofluorenyl, spirofluorenyl, etc. Any of the following, with dashed lines representing connection points.
[0034] Preferably, Ar1 is selected from any one of phenyl, naphthyl, diphenyl, 9,9-dimethylfluorenyl, dibenzofuranyl or dibenzothiopheneyl.
[0035] It should be noted that if m and n are both 1 in the compound shown in Formula I of this invention, then Ar1 is a disubstituent of the above-mentioned group.
[0036] As a preferred embodiment of the present invention, the C6-C20 aryl group is selected from any one of phenyl, biphenyl, naphthyl, phenanthryl, anthracene, fluorenyl, benzo[a]fluorenyl, triphenylene, fluoranyl, pyrene, perylene, indo[a]fluorenyl, or hydrogenated benzo[a]anthryl.
[0037] Preferably, the C1-C6 alkyl group is selected from any one of methyl, ethyl, propyl, or butyl.
[0038] Preferably, the C1-C6 alkoxy group is selected from any one of methoxy, ethoxy, propoxy, or butoxy.
[0039] Preferably, the hydrogen atom in the compound represented by Formula I can be substituted by at least one of phenyl, methyl, tert-butyl, methoxy, -F, -CN, -D, diphenyl, 9,9-dimethylfluorenyl, dibenzothiophene, dibenzofuranyl, fluoranyl, triphenylene, and naphthyl.
[0040] As a preferred embodiment of the present invention, the compound of formula I is selected from any one of the following compounds, whether substituted or unsubstituted:
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048] The substitution refers to the corresponding Ar1 or Ar2 in the above compounds. At least one hydrogen atom on an aryl group in one of the substituents is completely replaced by a deuterium atom; and / or in the above compounds All the hydrogen atoms on it are replaced by deuterium atoms.
[0049] In a second aspect, the present invention provides a compound for preparing the deuterated composition as described in the first aspect, said compound being selected from any one of the following compounds:
[0050]
[0051] In this invention, the compound of formula I is obtained through... The intermediate is prepared by a substitution reaction with an intermediate selected from any one of the following compounds:
[0052]
[0053]
[0054] Thirdly, the present invention provides an organic electroluminescent device in a process, the organic electroluminescent device comprising an anode, a cathode, and an organic thin film layer disposed between the anode and the cathode;
[0055] The organic thin film layer includes an electron transport layer, a light-emitting layer, a hole transport layer, and an electron blocking layer;
[0056] The material of the organic thin film layer includes the deuterated composition as described in the first aspect.
[0057] Preferably, the organic thin film layer includes a light-emitting layer, and the host material of the light-emitting layer includes the deuterated composition as described in the first aspect.
[0058] As a preferred embodiment of the present invention, the organic electroluminescent device is a red-light organic electroluminescent device.
[0059] Preferably, the organic electroluminescent device is a red phosphorescent organic electroluminescent device.
[0060] Fourthly, the present invention provides a display device comprising the organic electroluminescent device as described in the third aspect.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] In this invention, by designing the composition of the deuterated composition and further by using compounds with specific structural formulas together, and by using this deuterated composition as the organic thin film layer material of the OLED light-emitting device, the OLED light-emitting device has a lower driving voltage, higher current efficiency and longer lifespan. Detailed Implementation
[0063] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0064] Preparation Example 1
[0065] This preparation example provides intermediate 4-1 and its synthesis method, which is as follows:
[0066]
[0067] Under nitrogen protection, add 60 mL of toluene, 30 mL of ethanol, and 20 mL of water to a 250 mL three-necked flask, followed by 1.99 g (0.01 mol) of 2,3-dichloroquineoxarin and 2.19 g (0.01 mol) of... 2.12 g (0.02 mol) of sodium carbonate and 0.115 g (0.0001 mol) of tetrakis(triphenylphosphine)palladium were reacted at 40 °C for 2 hours, then at 60-70 °C for 4 hours. The mixture was cooled, water was added to dissolve the solid, the organic layer was washed with water, magnesium sulfate was dried, magnesium sulfate was removed by filtration, the solvent was removed by vacuum, and the obtained solid was recrystallized from toluene to give 2.8 g of the intermediate shown in Formula 4-1.
[0068] The intermediate shown in Equation 4-1 was subjected to mass spectrometry detection, and the m / z was measured to be 337.10.
[0069] The intermediate shown in Equation 4-1 was subjected to NMR detection, and the results were obtained. 1 H-NMR (Bruker, Switzerland, Avance II 400MHz nuclear magnetic resonance spectrometer, CDCl3): δ7.88 (m, 2H), δ7.71 (m, 2H).
[0070] Preparation Examples 2-6
[0071] Preparation Examples 2-6 each provide an intermediate (as shown in Table 1 below), the synthesis method of which is the same as the synthesis method of intermediate 4-1 in Preparation Example 1, the difference being that... The boronic acid compound was replaced with an equal amount of boric acid compound (see Table 1 for details), and in Preparation Example 5, 2,3-dichloroquinoxaline was replaced with an equal amount of boric acid compound. In Preparation Example 6, 2,3-dichloroquinoxaline was replaced with an equimolar amount of... The intermediate was then analyzed by mass spectrometry, and the m / z data of the test results are shown in Table 1 below:
[0072] Table 1
[0073]
[0074] Preparation Example 7
[0075] This preparation example provides a compound MD and its synthesis method, which is as follows:
[0076]
[0077] At room temperature, the compound shown in MC (5.5 g), palladium chloride (0.035 g), anhydrous nickel chloride (0.026 g), activated carbon (0.4 g), D2O (40 mL), and C6D6 (150 mL) were added to a 500 mL autoclave, and hydrogen gas was introduced into the autoclave until the pressure reached 0.02 MPa. The autoclave was then heated to 90 °C and reacted for 40 hours. After cooling to room temperature, the autoclave was filtered and separated. The organic layer after separation was dried with magnesium sulfate, decolorized by a short silica gel column, concentrated to dryness, and crystallized twice with toluene to obtain MD (4.6 g).
[0078] The intermediate shown in formula MD was subjected to mass spectrometry detection, and the m / z was measured to be 304.19.
[0079] Synthesis Example 1
[0080] This synthetic example provides compound 1 and its synthetic method, which is as follows:
[0081]
[0082] Under nitrogen protection, 200 mL of cyclohexanone, 3.0 g of the intermediate shown in Formula 1-1, 2.9 g of intermediate MC, 1.06 g of sodium carbonate, 0.2 g of cuprous oxide, and 0.001 g of palladium acetate were added to a 500 mL three-necked flask. The mixture was slowly heated to reflux for 12 hours. After cooling, water was added, and the resulting solid was filtered. After drying, the solid was dissolved in toluene by heating, hot filtered to remove insoluble matter, and the mother liquor was concentrated to dryness. The mixture was then separated by silica gel column chromatography, eluted with petroleum ether:dichloromethane:ethyl acetate = 10:3:1 (volume ratio), to give 4.1 g of compound 1.
[0083] Compound 1 was analyzed by mass spectrometry, and the m / z was 552.23.
[0084] Synthesis Examples 2-10
[0085] Synthesis Examples 2-10 provide compounds 2-6, 8, 10-11, and 11H, respectively. The synthesis methods are the same as those for compound 1 in Synthesis Example 1, except that intermediate 1-1 is replaced with an equal amount of the corresponding intermediate (see Table 2). In some synthesis examples, the compound shown in MC is replaced with an equal amount of the MD compound (see Table 2). The mass spectra of the synthesized compounds were measured and the m / z data were recorded. See Table 2 for details.
[0086] Table 2
[0087]
[0088]
[0089] Synthesis Example 11
[0090] This synthetic example provides compound 1 and its synthetic method, which is as follows:
[0091]
[0092] Under nitrogen protection, 80 mL of dry toluene, MD compound (3.0 g), intermediate 7-1 (3.16 g), Pd(dba)2 (bis(dibenzylacetone palladium, 0.0575 g), a 10% (w / w) toluene solution of tri-tert-butylphosphine (0.4 g), and sodium tert-butoxide (1.44 g) were added to a 250 mL three-necked flask. The mixture was slowly heated to reflux and reacted for 8 hours. After cooling to room temperature, water was added to dissolve the mixture. The organic layer was then washed with water until neutral, dried with magnesium sulfate, filtered to remove magnesium sulfate, concentrated to dryness, and separated by silica gel column chromatography. The eluent was petroleum ether:dichloromethane:ethyl acetate = 10:3:1 (v / v) to give 3.9 g of compound 7.
[0093] Mass spectrometry analysis of compound 7 showed a mass-to-charge ratio (m / z) of 583.28.
[0094] Synthesis Examples 12-17
[0095] Synthesis Examples 12-17 provide compounds 9, 7H, 12, 12H, 13, and 13H, respectively. The synthesis methods are the same as those for compound 7 in Synthesis Example 11, except that intermediate 7-1 is replaced with an equal amount of the corresponding intermediate chlorinated / brominated compound (see Table 3). In some synthesis examples, the compound shown in MC is replaced with an equal amount of the MD compound (see Table 3). The mass spectra of the synthesized compounds were measured, and the m / z data were recorded. See Table 3 for details.
[0096] Table 3
[0097]
[0098]
[0099] The specific structures of the compounds used in the following device embodiments are shown below:
[0100]
[0101]
[0102] Device Example 1
[0103] This embodiment of the device provides an organic electroluminescent device, which uses the deuterated composition provided by the present invention as the red light host material in the organic electroluminescent device. The structure of the organic electroluminescent device is: ITO / HT-1 (20nm) / red light host material (35nm): Ir(piq)3 [10%] / TPBI (10nm) / Alq3 (15nm) / LiF (0.5nm) / Al (150nm). Wherein "Ir(piq)3 [10%]" refers to the doping ratio of red light dye, that is, the volume ratio of red light host material to Ir(piq)3 is 90:10.
[0104] The organic electroluminescent device fabrication process is as follows: a glass plate coated with an ITO transparent conductive layer is ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone and ethanol, baked in a clean environment until all moisture is removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam.
[0105] The glass substrate with the anode was placed in a vacuum chamber and evacuated to a vacuum level of 1×10⁻⁶. -5 ~9×10 -3 Pa, a hole transport layer HT-1 is vacuum-deposited on the above-mentioned anodic layer film at a deposition rate of 0.1 nm / s and a film thickness of 20 nm.
[0106] A red light host material and dye Ir(piq)3 were vacuum-deposited on the hole transport layer as the light-emitting layer of the organic electroluminescent device. The deposition rate was 0.1 nm / s and the total film thickness was 35 nm. In this embodiment, compound 1 and compound 1H were placed in different evaporation sources and heated. The heating rate was controlled so that the volume ratio of the two deposited on the substrate was 1:1, which served as the red light host material.
[0107] Electron transport layers TPBI and Alq3 were sequentially vacuum-deposited on top of the light-emitting layer at a deposition rate of 0.1 nm / s, with film thicknesses of 10 nm and 15 nm, respectively.
[0108] 0.5 nm of LiF was vacuum-deposited on the electron transport layer, and 150 nm of Al was used as the electron injection layer and cathode.
[0109] Device Examples 2-6
[0110] Device Examples 2-6 each provide an organic electroluminescent device. The only difference between them and Device Example 1 is that the red light host material is different. The volume ratio of the two components in the red light host deposited on the substrate is 1:1 (see Table 4 for details). Other preparation steps and conditions are the same as those in Device Example 1.
[0111] Device Comparison Examples 1-10
[0112] Comparative Examples 1-10 each provide an organic electroluminescent device. The only difference between them and Device Example 1 is that the red light host material is a single compound (see Table 4 for details). The other preparation steps and conditions are the same as those in Device Example 1.
[0113] Performance testing:
[0114] The brightness, driving voltage, current efficiency, and lifetime (LT90) of the fabricated organic electroluminescent device were measured using an OLED-1000 multi-channel accelerated aging lifetime and photochromic performance analysis system manufactured by Hangzhou Yuanfang. The lifetime test (LT90) refers to maintaining a constant current density (1000 cd / m²) at room temperature (25–27°C) while retaining the initial brightness. 2 The time required for the brightness to decrease to 90% of the initial brightness. See Table 4 for detailed test data.
[0115] Table 4
[0116]
[0117]
[0118]
[0119] As shown in Table 4, the organic electroluminescent device prepared by using a combination of at least two compounds as the main material for red light in this invention has a lower driving voltage, higher current efficiency, and longer service life.
[0120] Compared to using single-component compounds as the main material for red light (device comparative examples 1-10), the composition used as the main material for red light in this invention has a similar composition and structure. Using this composition as the main material for the light-emitting layer improves its film-forming properties, resulting in higher charge mobility, stable device structure, improved voltage efficiency and lifetime of organic electroluminescent devices, and reduced driving voltage of organic electroluminescent devices.
[0121] Device Example 7
[0122] This embodiment of the device provides an organic electroluminescent device, using the compound provided by this invention as the hole transport material in the organic electroluminescent device. The structure of the organic electroluminescent device is: ITO / hole transport material (20nm) / red light host material (35nm): Ir(piq)3 [10%] / TPBI (10nm) / Alq3 (15nm) / LiF (0.5nm) / Al (150nm). Wherein "Ir(piq)3 [10%]" refers to the doping ratio of the red light dye, that is, the volume ratio of the red light host material to Ir(piq)3 is 90:10.
[0123] The organic electroluminescent device fabrication process is as follows: a glass plate coated with an ITO transparent conductive layer is ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone and ethanol, baked in a clean environment until all moisture is removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam.
[0124] The glass substrate with the anode was placed in a vacuum chamber and evacuated to a vacuum level of 1×10⁻⁶. -5 ~9×10 -3 Pa, a hole transport material is vacuum-deposited on the above-mentioned anode layer film at a deposition rate of 0.1 nm / s and a film thickness of 20 nm; in this embodiment, compound 12 and compound 12H are placed in different evaporation sources for heating, and the heating rate is controlled so that the volume ratio of the two deposited on the substrate is 1:1, which serves as the hole transport layer material.
[0125] A red light host material and dye Ir(piq)3 were vacuum-deposited on the hole transport layer as the light-emitting layer of the organic electroluminescent device. The deposition rate was 0.1 nm / s and the total film thickness was 35 nm. In this embodiment, compound 1 and compound 1H were placed in different evaporation sources and heated. The heating rate was controlled so that the volume ratio of the two deposited on the substrate was 1:1, which served as the red light host material.
[0126] Electron transport layers TPBI and Alq3 were sequentially vacuum-deposited on top of the light-emitting layer at a deposition rate of 0.1 nm / s, with film thicknesses of 10 nm and 15 nm, respectively.
[0127] 0.5 nm of LiF was vacuum-deposited on the electron transport layer, and 150 nm of Al was used as the electron injection layer and cathode.
[0128] Device Comparison Examples 11-12
[0129] Comparative Examples 11-12 each provide an organic electroluminescent device, which differs from Device Example 7 only in that the hole transport material is a single material (see Table 5 for details). The other preparation steps and conditions are the same as those in Device Example 7.
[0130] Performance testing:
[0131] The brightness, driving voltage, current efficiency, and lifetime (LT90) of the fabricated organic electroluminescent device were measured using the OLED-1000 multi-channel accelerated aging lifetime and photochromic performance analysis system manufactured by Hangzhou Yuanfang. The lifetime test LT90 refers to the time required for the brightness to decrease to 90% of the initial brightness while maintaining a constant current density (1000 cd / m²) at room temperature (25–27°C). Detailed test data are shown in Table 5.
[0132] Table 5
[0133]
[0134] As shown in Table 5, the electroluminescent device prepared by using a combination of at least two compounds as the hole transport layer material in this invention has a lower driving voltage, higher current efficiency, and longer service life.
[0135] As can be seen from Tables 4 and 5, using the composition provided by the present invention as both the red light host material and the hole transport layer material can further improve the current efficiency and lifespan of organic electroluminescent devices.
[0136] Device Example 8
[0137] This embodiment of the device provides an organic electroluminescent device, which differs from device embodiment 1 only in that the red light host material is different. In this embodiment, the red light host material is compound 5, compound 6, and compound 2H, and the volume ratio of the three is 1:1:1. When preparing the organic electroluminescent device in this embodiment, the three materials are placed in different evaporation sources for heating, and the heating rate is controlled so that the volume ratio of the three materials deposited on the substrate is 1:1:1 (see Table 6 for details). Other preparation steps and conditions are the same as those in device embodiment 1.
[0138] Device Example 9
[0139] This embodiment of the device provides an organic electroluminescent device, which differs from device embodiment 1 only in that the red light host material is different. In this embodiment, the red light host material is compound 5, compound 6, and compound 2, and the volume ratio of the three is 1:1:1. When preparing the organic electroluminescent device in this embodiment, the three materials are placed in different evaporation sources for heating, and the heating rate is controlled so that the volume ratio of the three materials deposited on the substrate is 1:1:1 (see Table 6 for details). Other preparation steps and conditions are the same as those in device embodiment 1.
[0140] Performance testing:
[0141] The brightness, driving voltage, current efficiency, and lifetime (LT90) of the fabricated organic electroluminescent device were measured using an OLED-1000 multi-channel accelerated aging lifetime and photochromic performance analysis system manufactured by Hangzhou Yuanfang. The lifetime test (LT90) refers to maintaining a constant current density (1000 cd / m²) at room temperature (25–27°C) while retaining the initial brightness. 2 The time required for the brightness to decrease to 90% of the initial brightness. See Table 6 for detailed test data.
[0142] Table 6
[0143]
[0144] A comparison of the data in Tables 4 and 6 shows that using a composition of three compounds as the main material for red light can further reduce the driving voltage of organic electroluminescent devices and improve their current efficiency and lifespan.
[0145] In summary, by designing the composition of the deuterated composition and further by using compounds with specific structural formulas together, and by using this deuterated composition as the organic thin film layer material for OLED light-emitting devices, the OLED light-emitting devices exhibit lower driving voltage, higher current efficiency, and longer lifespan.
[0146] The applicant declares that the detailed process flow of this invention is illustrated by the above embodiments, but this invention is not limited to the above detailed process flow, that is, it does not mean that this invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, addition of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of this invention.
Claims
1. A deuterated composition, characterized in that, The deuterated composition comprises at least two compounds, and at least one compound contains a deuterium atom; The compound is selected from the following compounds: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 2. An organic electroluminescent device, characterized in that, The organic electroluminescent device includes an anode, a cathode, and an organic thin film layer disposed between the anode and the cathode; The organic thin film layer includes an electron transport layer, a light-emitting layer, a hole transport layer, and an electron blocking layer; The material of the organic thin film layer includes the deuterated composition as described in claim 1.
3. The organic electroluminescent device according to claim 2, characterized in that, The organic thin film layer includes a light-emitting layer, and the main material of the light-emitting layer includes the deuterated composition as described in claim 1.
4. The organic electroluminescent device according to claim 2, characterized in that, The organic electroluminescent device is a red-light organic electroluminescent device.
5. The organic electroluminescent device according to claim 2, characterized in that, The organic electroluminescent device is a red phosphorescent organic electroluminescent device.
6. A display device, characterized in that, The display device includes an organic electroluminescent device as described in any one of claims 2-5.
Citation Information
Patent Citations
Organic electroluminescent compound, preparation method thereof and electroluminescent device
CN111057014A
A plurality of host materials and organic electroluminescent device comprising the same
CN112352325A
Organic electroluminescent device
WO2020050576A1